Issues and Trends in Online Purchases in the Malaysian Halal Cosmetics Industry - Roszi Naszariah Nasni Naseri, Norfaridatul Akmaliah Othman (International Journal of Advanced Science and Technology, 2020)
The global halal industry has emerged as a new sector in the global economy that is rapidly expanding and establishing a strong presence in various developed countries. At present, the halal industry has expanded beyond food products and is further tapping into the economic potential of halal cosmetic products. This paper aims to enhance the understanding of the concept and definition of halal cosmetic products and provide an overview of the issues and current trends in e-commerce in the global arena and more specifically, Malaysia. This study also highlights some of the halal cosmetic products that have been successfully sold through e-commerce platforms. Owing to the growing importance of halal-certified cosmetics and personal care products, this review addresses the current state of the halal cosmetics industry and e-commerce developments in the halal cosmetics sector.